Предмет: Математика,
автор: Kristi546
Помогите упростить выражение b+(b+12)+(b+12*2)
Ответы
Автор ответа:
0
b+(b+12)+(b+12×2)=b+b+12+(b+24)=b+b+12+b+24=3b+36
Автор ответа:
0
у вас там опечатка,3b+36 )
Автор ответа:
0
спасибо))
Автор ответа:
0
b+(b+12)+(b+12×2)=b+b+12+(b+24)=b+b+12+b+24=3b+36
Похожие вопросы
Предмет: Биология,
автор: cecoevroma3
Предмет: Українська література,
автор: myaskovskyimaxym
Предмет: История,
автор: KRUT0Y
Предмет: Математика,
автор: аня484
Предмет: Математика,
автор: богвик